The magic school bus : inside the Earth - Cole, Joanna; Degen, Bruce (New York : Scholastic Inc., 2004)
On a special field trip in the magic school bus, Ms Frizzle's class learn at first hand about different kinds of rocks and the formation of the earth.
G2
Keywords: Physical geology -- Juvenile literature; Geology; Earth -- Internal structure